Pseudomonas aeruginosa prosthetic joint-infection outcomes: Prospective, observational study on 43 patients - Prié, Héloïse; Meyssonnier, Vanina; Kerroumi, Younes; Heym, Beate; Lidove, Olivier; Marmor, Simon; Zeller, Valérie (Frontiers in Medicine, 2022)
Objectives: Analysis the outcomes of P. aeruginosa prosthetic joint infection (PJIs), their clinical and microbiological characteristics, surgical strategies and antibiotic treatments. Methods: Monocenter cohort study in a Bone-and-Joint-Infection Referral Center (08/2004-10/2018) including all consecutive P. aeruginosa PJIs. Data were extracted from the prospective database: relapses, new PJIs, related deaths. Results median [IQR]: Among the 43 patients included (28 females; 72 [63-80] years old; 27 hip, 15 knee and 1 shoulder PJIs), 29 (67%) had underlying comorbidities, 12 (28%) had previously been treated for another PJI, 9 (21%) had undergone previous surgeries for their P. aeruginosa PJI. Eleven (26%) PJIs were polymicrobial, 16 (37%) strains were wild type, 8 (19%) ciprofloxacin-resistant. PJIs were classified as late chronic (n=33), early postoperative (n=9), acute hematogenous infection (n=1). Forty patients underwent surgery: 27 one-stage, 5 two-stage exchanges, 3 debridement and implant retention, 5 other surgical strategies. Antibiotic treatments were: 29 received 41 [37-43] days of combination therapy (IV anti-pseudomonal β-lactam and 3–5 days of amikacin, then β-lactam and oral ciprofloxacin), followed by oral ciprofloxacin for a total of 12 weeks; 10 received only IV antibiotics for 83 [77-86] days, including 37 [32-46] days of combination therapy; 49 days of ceftazidime alone for 1. During follow-up lasting 33 [24-64.5] months, 2 relapses, 3 new PJIs and 2 related deaths occurred. Thirty-three (82%) patients and 93% of those managed with one-stage exchange experienced no event. Conclusions: Outcomes of our cohort’s P. aeruginosa PJIs—predominantly monomicrobial, chronic, ciprofloxacin-susceptible, treated with one-stage exchange and prolonged IV antibiotics—were 82% favorable.